The Effect Of Finger Relaxation Techniques On Anxiety In Pregnant Women - Leli Leli; Warda M; Rahayu Setyaningsih; Yunita Suriani Suardi (International Journal of Health Sciences, 2026)
Anxiety is a psychological problem often experienced by pregnant women, especially in the final trimester, and can negatively impact the health of both the mother and the fetus. One non-pharmacological intervention that can be used to reduce anxiety is the finger relaxation technique. This study aimed to determine the effect of the finger relaxation technique on anxiety levels in pregnant women. The study used a quasi-independent design. experiment with a pretest – posttest approach without control the study sample consisted of 40 pregnant women selected using purposive sampling. Anxiety levels were measured using an anxiety questionnaire before and after the finger relaxation technique intervention. Data analysis was performed using a paired t - test. The results showed a significant decrease in anxiety levels in pregnant women after the finger relaxation technique (p < 0.05). It was concluded that the finger relaxation technique is effective in reducing anxiety levels in pregnant women and can be used as an alternative nursing and midwifery intervention.